Analisis Literatur Faktor Penyebab dan Dampak Negatif Perilaku Agresif Tawuran pada Remaja di Indonesia - Tabitha Zahra; Hany Natari Adha; Risma Anita Puriani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Teenage brawls have become an increasingly urgent social issue, considering the destructive impact they cause. This study aims to explore the causes and negative impacts of student brawls through a literature review. By analyzing 20 related academic articles, it was found that the triggers of brawls can be divided into two main dimensions. The internal dimension includes factors such as deindividuation, identity crisis, and low self-regulation, while the external dimension encompasses ineffective parenting styles, peer influence, and provocation through social media. The impact of brawls is significant, not only on physical aspects and fatalities but also on psychological disturbances, moral decline, stigmatization, and serious legal consequences. This study concludes that a comprehensive intervention approach is needed, involving school counseling services, education on better parenting, and community monitoring to reduce the tendency for teenage aggression. This strategy is expected to address the root causes of brawls in a more structured and effective manner, creating a safer environment and supporting positive teenage development.